Integrated physiological and metabolomic responses reveal mechanisms of Cd tolerance and detoxification in kenaf (Hibiscus cannabinus L.) under Cd stress - Saeed, Wajid; Mubeen, Samavia; Pan, Jiao; Rehman, Muzammal; Fang, Wangqiang; Luo, Dengjie; Liu, Pingwu; Li, Yun; Chen, Peng (Frontiers in Plant Science, 2024)
Introduction Cadmium (Cd) is a highly toxic trace element that occurs in large quantities in agricultural soils. The cultivation of industrial crops with high phytoremediation potential, such as kenaf, could effectively reduce soil Cd contamination, but the mechanisms of toxicity, tolerance, and detoxification remain unclear. Methods In this study, the effects of different Cd concentrations (0, 100, 250, and 400 µM) on growth, biomass, Cd uptake, physiological parameters, metabolites and gene expression response of kenaf were investigated in a hydroponic experiment. Results and discussion The results showed that Cd stress significantly altered the ability of kenaf to accumulate and transport Cd; increased the activity of hydrogen peroxide (H2O2), superoxide anion (O2−), and malondialdehyde (MDA); reduced the activities of superoxide dismutase (SOD) and catalase (CAT); and decreased the content of photosynthetic pigments, resulting in significant changes in growth and biomass production. Exposure to Cd was found to have a detrimental effect on the ascorbate–glutathione (AsA–GSH) cycle in the roots, whereas it resulted in an elevation in AsA levels and a reduction in GSH levels in the leaves. The increased content of cell wall polysaccharides under Cd stress could contribute to Cd retention in roots and limited Cd transport to above-ground plant tissues. Metabolomic analyses revealed that alanine, aspartate, and glutamate metabolism, oxidative phosphorylation, ABC transporter, and carbon metabolism were the major metabolic pathways associated with Cd stress tolerance. Cd stress increased gene expression of IRT1 and MTP1 in roots, which resulted in kenaf roots accumulating high Cd concentrations. This study extends our knowledge of the factors regulating the response of kenaf to Cd stress. This work provided a physiological and metabolomic perspective on the mechanism controlling the response of kenaf to Cd stress.